(3OjhGf GdWHs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3bGd CHh Sgd gPG gh GdcJGH GdChd ef cJHfG ai UfGYI GdWH hbUOfG ajg Cf fJcde ajeG jLH JbOjeg bHd GdTQhY ai Yde GdWH s
(3BNQgG (B:s
(3ChUjg ai Mdbg bgQkG hPdc EPG CNP HaRY ef GdeGA hJMV YfO Pdc HGddHf heGA GdTYjQ hOgf GdHfaSL hggfG adfbWY GdcdGe ai gPG GdHGH Je s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO (B(5141) s
Keywords: (3GdWHs